IMPLEMENTASI NILAI PENDIDIKAN KARAKTER DALAM TRADISI SISINGLAR LEMBUR : STUDI KASUS PARTISIPASI SISWA SEKOLAH DASAR DI KECAMATAN KAWALI KABUPATEN CIAMIS - Nurul Ilmi Pujawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Elementary schools are formal institutions that serve as the first crucible for instilling good character in children. The content of character values, combined with character values, shapes students' identities, each with its uniqueness. Values and culture derived from local wisdom in a particular region serve as one of its philosophical foundations. This study analyzes the implementation of Islamic character values in the Sisinglar Lembur implementation through the participation of elementary school students in Kawali. Using a qualitative case study approach based on Social Learning Theory, this study reveals how tradition functions as an arena for social learning. Results indicate that students internalize the values of mutual cooperation, respect, and responsibility through modeling by adults and reinforcement of representation. The mechanisms of attention, retention, reproduction, and motivation are proven effective, making local wisdom a living curriculum for character building.